(When) does money growth help to predict Euro-area inflation at low frequencies? - Sven Schreiber (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
Short answer: It helps a lot when other important variables are excluded from the information set. Longer answer: We revisit claims in the literature that money growth is Granger-causal for inflation at low frequencies. Applying frequency-specific tests in a comprehensive system setup for euro-area data we consider various theoretical predictors of inflation. A general-to-specific testing strategy reveals a recursive structure where only the unemployment rate and long-term interest rates are directly Granger-causal for low-frequency inflation movements, and all variables affect money growth. We therefore interpret opposite results from bivariate inflation/money growth systems as spurious due to omittedvariable biases. We also analyze the resulting four-dimensional system in a cointegration framework and find structural changes in the long-run adjustment behavior, which do not affect the main conclusions, however.
Keywords: E31; E40; 330; money growth; granger causality; quantity theory; unemployment